DETERMINAN KEJADIAN STROKE BERULANG - Wulandari, Angernani Trias; Fadila, Erida; Santoso, Raden Bagus Edy; Unok, Warihan (Ensiklopedia of Journal, 2025)
Abstract: Stroke is the second leading cause of death in Indonesia after heart disease, with the incidence rate increasing every year. Based on data search from Stella Maris Hospital Makassar, it is known that the number of stroke patients totals 168 people. Patients who experienced recurrent stroke amounted to 43 people. While patients who died from recurrent stroke amounted to 17 people. The purpose of this study was to determine the determinants of recurrent stroke. The research design used in this study is Case Control. The research was conducted at Stella Maris Hospital Makassar. The research was conducted in March 2023. The study population was patients who had a stroke and who were in the Stella Maris Makassar Hospital area who met the criteria that could be studied. The sample amounted to 53 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed a relationship between age (p value: 0.048) and history of hypertension (p value: 0.000). It is suggested that the hospital can publicize to the wider community the impact caused by hypertension if not treated properly and quickly because it can lead to stroke.Keywords: Hipertensi, Stroke, Age.